ChemInform Abstract: Chemoenzymatic Synthesis and Evaluation of 3‐Azabicyclo[3.2.0]heptane Derivatives as Dopaminergic Ligands. Issue 3 (22nd January 2013) - Reinart‐Okugbeni, Reet; Ausmees, Kerti; Kriis, Kadri; Werner, Franz; Rinken, Ago; Kanger, Tonis
Abstract New 3‐azabicycloheptane derivatives (IV) are synthesized via a multicomponent cascade reaction and resolved by kinetic enzymatic resolution with immobilized lipase B.